Nano-architectured cobalt selenide spheres anchored on graphene oxide sheets for sodium ion battery anode - Ali, Zeeshan; Ali, Muhammad; Mehmood, Ahtisam; Ishfaq, Ayesha; Akram, Muhammad Aftab; Zeb, Akif; Lin, Xiaoming (Frontiers in Materials, 2022)
Aimed at commercializing the technology of sodium-ion batteries (SIBs), researchers have been trying to produce electrode materials with optimally high charge storage capacity, superior rate capability, extended life, and cost-effective components. Herein, we synthesized an electrode of cobalt selenides loaded in carbon spheres and anchored on reduced graphene (CSSs@rGO) for high-performance SIBs. This improved structure of CSSs@rGO permits the pseudocapacitive storage of charge, thus enhancing the electrical characteristics. It was discovered that the diameter of the carbon sphere had a significant impact on the charge storage capacities of the developed electrode materials, suggesting the probable depth of sodium-ion (Na-ion) movement in the electrode materials during charge and discharge. For instance, CSSs@rGO with an average diameter of ∼70 nm presented the best electrochemical performance as an anode of SIBs. The nano-architecture CSSs@rGO exhibits excellent ion storage capability with a reversible capacity of 600 mA h g-1 at a discharge rate of 100 mA g−1 after 50 cycles. However, at a higher discharge rate (e.g., 1,000 mA g−1), a storage capacity as high as 380 mA h g−1 was achieved. In addition to higher charge storage capability and efficient charge storage at higher discharge rates, the developed CSSs@rGO exhibited stable cycling performance for over 3,000 cycles, which clearly shows the feasibility of our products. This work will open new approaches for developing advanced electrode materials for high-performance sodium-ion batteries.